Effects of binary vacuum residue blending ratios on the product yields in a delayed coking process. (3rd June 2017) - Torabi Esfahani, Farshad; Ehsani, Mohammad Reza; Ivakpour, Javad
ABSTRACT: Blending of different hydrocarbon cuts is a common procedure in refining processes such as thermal cracking units. Blending could affect the products properties considerably. In this work, four binary blends of Iranian vacuum residues are prepared and thermally cracked at 500°C for 2 h in a batch atmospheric delayed coking reactor. Product yields have been defined for different blending ratios. Results show that the yields of liquid products have considerable deviations compared to the simple mixing rule. These deviations could be positive or negative compared to the simple mixing rule. The deviations could also be justified by SARA (saturate, aromatic, resin, asphaltene) analysis of blends. A new method has been proposed to predict the sign of deviation based on metals and sulfur contents.